Strengthening Postharvest Technology Development and Improvement Through Feedback - Adegbola; Owojaiye, J. A.,; Ogunremi, O. B.,; Aina, O. B.,; Achime, O. B.,; Pessu, K. C. and (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
This inquiry is predicated on the datum or truism that all technologies have a gap and or become obsolete at some point, and the utilization of passé technologies and methods predisposes the agricultural sector to underdevelopment. It investigates technological paucities and fixes for NSPRI technologies (NSPRI Smoking Kiln (NSK), Parabolic-shaped Solar Dryer (PSSD), Ice Fish Box® (IFB®), Hermetic Steel Drum (HSD) and Ventilated Plastic Crate (VPC)) from the perspective of users of the technologies. The study adopted a cross-sectional research design using the in person method as its feedback mechanism in 18 states across 6 geopolitical zones in Nigeria. Data were obtained through interview schedules supplemented with key informant interviews while a multi-stage sampling procedure was employed in the selection of respondents. Firstly, eighteen (18) States where NSPRI postharvest technologies have been disseminated and adopted were purposively selected. Secondly, users of improved NSPRI postharvest technologies were selected from diverse locations within the states earlier selected. Non-probabilistic techniques particularly snowballing were also employed at this stage. Frequencies, percentages, means and weighted averages were employed in the analysis of data components. Results showed that 70% of respondents have never provided feedback on NSPRI technologies. Executives of various associations was used by 45% of NSK users, 59% of IFB users, and 48% of VPC users to provide feedback while 43% of PSSD users and 40% of HSD users shared opinions through NSPRI extension staff. In general, there exists a strong (NSK: 94% PSSD: 95.2% IFB®: 91% HSD: 88.6% VPC: 74.5%) willingness to recommend technologies among respondents even as they provided positive feedback on use parameters and components of the technologies. However, respondents opined that the roller and chimney (NSK), durability of polypropylene cover (PSSD), draining of thawed ice (IFB®), and bolted ring (HSD) require improvement.